A novel hybrid actuation mechanism based XY nanopositioning stage with totally decoupled kinematics. (15th January 2018) - Zhu, Wu-Le; Zhu, Zhiwei; Guo, Ping; Ju, Bing-Feng
Highlights: A novel XY nanopositioning stage is proposed with comprehensive investigation. A hybrid actuation mechanism is proposed with greatly improved performance. Finite element analytical model is introduced for elastic deformation modeling. Closed-loop control of the PEA by integrating strain gauge is validated for the elimination of hysteresis of the stage. Abstract: This paper reports the design, analysis and testing of a parallel two degree-of-freedom piezo-actuated compliant stage for XY nanopositioning by introducing an innovative hybrid actuation mechanism. It mainly features the combination of two Scott–Russell and a half-bridge mechanisms for double-stage displacement amplification as well as moving direction modulation. By adopting the leaf-type double parallelogram (LTDP) structures at both input and output ends of the hybrid mechanism, the lateral stiffness and dynamic characteristics are significantly improved while the parasitic motions are greatly eliminated. The XY nanopositioning stage is constructed with two orthogonally configured hybrid mechanisms along with the LTDP mechanisms for totally decoupled kinematics at both input and output ends. An analytical model was established to describe the complete elastic deformation behavior of the stage, with further verification through the finite element simulation. Finally, experiments were implemented to comprehensively evaluate both the static and dynamic performances of the proposed stage. Closed-loop control of the piezoelectric actuators (PEA) by integrating strain gauges was also conducted to effectively eliminate the nonlinear hysteresis of the stage.